Fractional statistical theory and use of quasi-chemical approximation for adsorption of interacting k-mers - Davila, Mara Veronica (2009)
In a recent paper [J.L. Riccardo, A. J. Ramirez-Pastor, F. Romá, Phys. Rev. Lett. 94 (2004) 186101], a new fractional statistical theory of adsorption (FSTA) based on Haldane's statistics was presented. Later [M. Dávila, F. Romá, J.L. Riccardo, A.J. Ramirez-Pastor, Surf. Sci. 600 (2006) 2011], a generalization of the classical quasi-chemical approximation (QCA) was developed in which the adsorbate can occupy more than one adsorption site. In this paper, we describe the statistical thermodynamics of interacting polyatomic adsorbates (k-mers) on homogeneous surfaces, by combining FSTA and QCA. The main thermodynamic functions are obtained in terms of two parameters, g and a, which are related directly to the spatial configuration of a polyatomic molecule in the adsorbed state. Analysis of simulated and experimental results have been carried out in order to (i) explore the reach and limitations of the theoretical model and (ii) evince the physical significance of g and a.